Pelanggaran Etika Pariwara Indonesia dalam Iklan Reklame Pengobatan Batara di Yogyakarta - Putra, Royan Zanuar; Prasetyo, Rayhan Tri; Fikri, Imam Ikhsanul; Sukmono, Filosa Gita (Jurnal Audiens, 2025)
This research aims to identify ethical violations in the advertisement of "BATARA Treatment," using a qualitative approach. The results of this study indicate that the Batara medicine advertisement has violated the Indonesia Advertising Ethics and the Consumer Protection Law, particularly regarding claims about treatment results that can be directly observed on-site and the placement of the advertisement, which does not comply with aesthetic rules and public order. This research highlights the importance of ethics in advertising to protect consumers.